Pediatric Lens Diseases - Liu, Yizhi; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book focuses on disorders of the lens, which are a major cause of blindness in children. During development, children$1 (Bs eyes have unique physiological and structural characteristics, such as an immature blood-aqueous barrier, which presents considerable challenges for ophthalmologists involved in the diagnosis and treatment of pediatric lens disorders. Throughout the book, the pathology, examination, anesthesia, surgical treatment and nursing care of pediatric lens disorders are discussed in detail. It not only presents diverse pictures and images from clinical practice, it also includes the latest findings in the field. It will be of interest to ophthalmologists and paediatricians looking to improve the diagnosis and treatment of pediatric lens disorders and provide a valuable reference resource for all those involved in ophthalmic clinical practice, teaching and research. Yizhi Liu is a professor and director of Zhongshan Ophthalmic Center, Sun Yat-sen University, China and he is also the director of State Key Laboratory of Ophthalmology at Zhongshan Ophthalmic Center, China.s
Embryonic Development of the Human Lens -- Human Visual Development -- Anatomy and Physiology of the Crystalline Lens -- Etiology of Pediatric Lens Diseases -- Epidemiology of Pediatric Cataracts -- Classification and Morphology of Pediatric Cataracts -- Overview of Pediatric Cataract Treatments -- History Taking and Specialized Examination of Lens Diseases in Children -- Perioperative Challenges and Solutions in the Management of Children with Cataracts -- General Anesthesia in Pediatric Lens Surgery -- Care of Pediatric Lens Surgery -- Pediatric Cataract Extraction -- Calculation and Selection of Intraocular Lens Power for Children -- Selection of Intraocular Lenses for Children -- Pediatric Intraocular Lens Implantation -- Cataract Surgery in Children with Anomalies of Uvea -- Ectopia Lentis in Children -- Cataract Surgery in Children with Preexisting Posterior Capsular Defects -- Surgery of Congenital Cataracts Associated with Persistent Fetal Vasculature -- Pediatric Cataract Surgery in Microphthalmic Eyes -- Lens Trauma in Children -- Intraoperative Complications and Management -- Postoperative Complications and Management -- Prevention and Management of Pediatric Secondary Cataracts -- Reposition, Explantation, and Exchange of Intraocular Lenses -- Postoperative visual rehabilitation in children with lens diseases -- Quality of Life Assessment in Children with Lens Anomalies.
Keywords: Medicine; Ophthalmology; Pathology; Pediatric surgery; Medicine & Public Health; Ophthalmology; Pediatric surgery; Pathology